Accounting for macro-finance trends: Market power, intangibles, and risk premia - Emmanuel Farhi; François Gourio (Federal Reserve Bank of Chicago, 2018)
Real risk-free interest rates have trended down over the past 30 years. Puzzlingly in light of this decline, (1) the return on private capital has remained stable or even increased, creating an increasing wedge with safe interest rates; (2) stock market valuation ratios have increased only moderately; (3) investment has been lackluster. We use a simple extension of the neoclassical growth model to diagnose the nexus of forces that jointly accounts for these developments. We .nd that rising market power, rising unmeasured intangibles, and rising risk premia, play a crucial role, over and above the traditional culprits of increasing savings supply and technological growth slowdown.
Keywords: E34; G12; 330; equity premium; risk-free rate; investment; profitability; valuation ratios; labor share; competition; markups; safe assets